Health inequalities and the health of the poor : what do we know? What can we do ? - Gwatkin, D.R. (2000)
Proposes two steps for action viz. that professionals who give very high priority to the distinct but related objectives of poverty alleviation, inequality reduction, and equity enhancement recognize that their shared concern for the distributional aspects of health policy is far more important than any differences that may divide them; secondly that health policy goals, currently expressed as societal averages, be reformulated so that they point specially to conditions among the poor and to poor-rich differences.